2002
DOI: 10.1359/jbmr.2002.17.4.630
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Osteoclast Differentiation by Daidzein via Caspase 3

Abstract: Phytoestrogens are plant-derived compounds with estrogen-like activity. Phytoestrogen-rich diets may prevent postmenopausal osteoporosis and these molecules maintain bone mass in ovariectomized animals. We compared the effects of the isoflavone daidzein, which has no action on tyrosine kinases, and 17␤-estradiol on the development and activity of osteoclasts in vitro. Nonadherent porcine bone marrow cells were cultured on dentine slices or on culture slides in the presence of 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 74 publications
3
54
1
Order By: Relevance
“…Isoflavone phytoestrogens stimulate osteoblastic bone formation, inhibit osteoclastic bone resorption (52), and prevent overall bone loss in ovariectomized rats or mice (55,85). Suggested mechanisms for these effects include stimulation of proliferation of osteoblast (bone forming) cells and protection of such cells from oxidative damage, and increased apoptosis of osteoclast (bone destroying) progenitor cells (112,154,196).…”
Section: Potential Health Beneficial Effects Of Isoflavonoid Phytoestmentioning
confidence: 99%
“…Isoflavone phytoestrogens stimulate osteoblastic bone formation, inhibit osteoclastic bone resorption (52), and prevent overall bone loss in ovariectomized rats or mice (55,85). Suggested mechanisms for these effects include stimulation of proliferation of osteoblast (bone forming) cells and protection of such cells from oxidative damage, and increased apoptosis of osteoclast (bone destroying) progenitor cells (112,154,196).…”
Section: Potential Health Beneficial Effects Of Isoflavonoid Phytoestmentioning
confidence: 99%
“…8,9) Compared with estradiol, iso‰avones have both estrogenic and anti-estrogenic eŠects. 10) Most of the estrogenic eŠects of daidzein to prompt bone formation and prevent bone resorption 11,12) have been observed in animal models and cultured cells. On the action of daidzein on bone formation, daidzein is shown to stimulate protein synthesis, alkaline phosphatase (ALP) activity and DNA content after the culture in osteoblast-like MC3T3 E1 cells for 2 days.…”
Section: Introductionmentioning
confidence: 99%
“…(Arikan et al, 2011;Prentice et al, 2006;Macdonald et al, 2004;Macdonald et al, 2008;Palacios et al, 2006;Tucker et al, 1999;Lister et al, 2007;New, 2003;Trzeciakiewicz et al, 2009 Numerous studies have shown the health-promoting properties of polyphenols, providing additional mechanisms through which they promote skeletal health by reducing resorption caused by high oxidative stress (Trzeciakiewicz et al, 2009;Tucker, 2009;Hunter et al, 2008). The antioxidant properties of polyphenols have been widely studied and reported in the literature (Liu et al, 2005;Miyamoto et al,1998;Rassi et al, 2002;Viereck et al, 2002;Ward et al, 2001;. They strongly support the role of polyphenols in the delayed onset or reduction in the progression of osteoporosis.…”
Section: Introductionmentioning
confidence: 94%